Size-dependent molecular interaction of nontraditional 2D antibiotics with Staphylococcus aureus. (1st January 2023) - Najafi, F; Ahmadi, H; Maghsoumi, A; Huma, K; Amini, A; Azimi, L; Karimi, A; Bayat, M; Naseri, N
Abstract: The application of nanomaterials for their antibacterial properties is the subject of many studies due to antibiotic resistance of pathogen bacteria and the necessity of omitting them from food and water resources. Graphene oxide (GO) is one of the most popular candidates for antibacterial application. However, the optimum condition for such an effect is not yet clear for practical purposes. To shed light on how GO and bacteria interaction depends on size, a wide range of GO flake sizes from hundreds of µm 2 going down to nano-scale as low as 10 N m 2 was produced. In an in-vitro systematic study to inhibit Staphylococcus aureus growth, the correlation between GO flake size, thickness, functional group density, and antibacterial activity was investigated. The GO suspension with the average size of 0.05 µm 2, in the order of the size of the bacteria itself, had the best bacteriostatic effect on S. aureus with the minimum inhibitory concentration value of 8 μg ml −1, well within the acceptable range for practical use. The bacteriostatic effect was measured to be a 76.2% reduction of the colony count over 2 h of incubation and the mechanism of action was the wrapping and isolation of cells from the growth environment. Furthermore, in-vivo animal studies revealed that 16 μg ml −1 of the optimum GO has efficient antibacterial performance against the methicillin-resistant strains of the bacteria with an enhanced wound healing rate and tensiometrial parameters which is important for realized targets.